Pivotal contemporary trials of percutaneous coronary intervention vs. coronary artery bypass grafting: a surgical perspective - Ngu, Janet M. C.; Sun, Louise Y.; Ruel, Marc (Annals of Cardiothoracic Surgery; Vol 7, No 4 (July 31, 2018): Coronary Revascularisation—Cardiology for the Surgeon, 2018)
Coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are the two revascularization strategies for patients with coronary artery disease (CAD). While CABG continues to be the gold standard for revascularization, advancements in PCI technology have triggered numerous, often industry-funded investigations to challenge this role. This perspective will provide a summary of previous RCTs comparing CABG vs. PCI. The recently published NOBLE and EXCEL trials will be discussed in depth. Future directions of research pertaining to CABG vs. PCI will be briefly discussed in this document.